Strategi Amerika Serikat dalam Membendung Kebangkitan Tiongkok di Asia Pasifik melalui Aliansi Pertahanan Quadrilateral Periode 2017-2020 - Mohamad Reza Tri Satriakhan; Edy Prasetyono (PERSPEKTIF, 2022)
This paper aims to find out the strategic role of the US Quadrilateral Security Alliance in reducing China's threats in the Asia Pacific during 2017-2020. The method used in this research is qualitative, with descriptive-analytical technique. This technique aims to provide a holistic understanding and description of a symptom or phenomenon. The findings of this study show that the rise of China in the economic and military sectors, as well as China's aggressiveness in expanding its territories, threatens the US hegemony in the Asia Pacific. Thus, to maintain its status quo, the US formed a Quad Alliance with Australia, Japan and India in 2007. However, this alliance was inactive since 2008 and reactivated in 2017 by President Donald Trump. The Quad Alliance is quite intense in conducting military expeditions in the Indian-Pacific Ocean. Based on the Balance of Threat theory by Stephen Walt (1985), the Quad Alliance is the US "Rebalancing Strategy" against China in the Asia Pacific, which aims to eliminate 4 main sources of threats, namely China's aggregate power, China's geographical proximity to the US alliance, China's military capabilities, and China's ambitions in the region. The dynamics of the Sino-US contestation are driven by the basic motive of Neorealism, that is protecting the national interests of the two countries, whether political, economic, or domination/influence.